Industry - An Urban Developer. Case Study: Iron and Steel Industry in Romania - Radu SĂGEATĂ (Transylvanian Review of Administrative Sciences, 2013)
The profound economic and social changes that took place during the period of transition from a central-based economy to the market system have deeply marked the evolution of industrial towns, particularly those targeted for heavy industry development between 1950 and 1989. The present paper analyses this model of urban evolution affected by the interference of the political-ideological factor. Three towns, Galaţi, Târgovişte and Oţelu Roşu, in which a strong iron-and-steel industry was planted, have been taken into the study. Galaţi – a large town with complex functions, a regional and crossborder polarization center, was singled out for this type of industry by political decision within the context of the industrialization drive of the 1950s; Târgovişte – an old middle urban center, was pushed into the iron-and-steel route in the 1970-1980 decade. Oţelu Roşu – a small town, has a traditional iron-and-steel industry based on local raw material resources. Relying on historical documents, bibliographical sources and field work, the author correlates urban development evolutions with the industrialization policies, highlighting the causes that have led to the present decline of these towns and the challenges facing the local authorities in revitalizing them in a sustainable manner.